IMPACT DES ASSURANCES AUTOMOBILES ET INCENDIES SUR LES RECETTES GLOBALES DE LA SONAS-ISIRO De 2006 à 2016 - Benjamin , AKEMANI AWENDE (IJRDO - Journal of Business Management, 2021)
Any company producing goods or service pursues the same goal of maximization of profit that passes the increase of revenue and minimization of costs, the SONAS Agency of Isiro can not do without this objective as a rational economic agent who has received the mission on the part of the State and to enjoy a monopoly in the insurance market to the national extent more than five decades. It is to be noted that SONAS is being hit by internal difficulties related to its management and external related to the low level of income of the population, ignorance of the property based insurance in the socio-economic life of household. All these hazards also justifies the low revenue mobilization of the Isiro agency SONAS.